Development, Validation, and Feasibility Testing of an Integrative Therapy Module for Obesity - Banusri, M; Patil, Suchitra S (International Research Journal of Ayurveda & Yoga, 2025)
Background: Obesity is a condition where the accumulation of excess fat in the body takes place. Obesity is a metabolic disorder caused due to defects in food and unhealthy lifestyle, and other causes are thyroid and pituitary gland secretion abnormalities, etc., which regulate fat and lipid metabolism in the body. Obesity is the casual factor of various diseases such as heart disease, diabetic mellitus, osteoarthritis, and certain cancers. The integration module of yoga, Ayurveda, and naturopathy may reduce the weight of individuals and hence reduce the cause of other diseases due to obesity. Objectives: To develop and validate of integrated module for obesity, to improve the quality of life, to reduce the weight, to check the psychological issues like stress and depression, to check the effect of integrated therapy of obesity on vikriti of kapha on obese individuals. Methods: The integrated module validation was done by 60 experts of Ayurveda, yoga, and naturopathy using the methods of Lawshe’s formula: Content validity ratio (CVR) = (Ne-N/2)/N/2, 30 sample size was taken for feasibility testing. Where Ryff scale, mindful attention awareness scale, and vikriti questionnaire were taken for analyzing the score. Results: 51 integrated module practices are selected for validation, 38 IAYT practices are selected for validation, 46 practices had a CVR score of ≥0.4 indicating high score validity, 5 practices are with low score <0.4 Conclusion: The integrated module of yoga, naturopathy, and Ayurveda has not only a definite role in weight reduction, improved quality of life, and psychological factors but also improved physical activities, emotional status, and social well-being.